Simplify. Remove grouping symbols and combine like terms. A) 5[3a-2a(3a+6b)+6a^2]

Expert Answers
jeew-m eNotes educator| Certified Educator

`5[3a-2a(3a+6b)+6a^2]`

`= 5[3a-6a^2-12ab+6a^2]`

`= 5(3a-12ab)`

`= 15a-60ab`

 

So the answer is;

`5[3a-2a(3a+6b)+6a^2] = 15a-60ab`

atyourservice | Student

`5[3a-2a(3a+6b)+6a^2]`

`5(3a-6a^2-12ba+6a^2)` you can distribute the 5 then combine like terms or combine like terms then distribute the 5

5(3a-6a^2+6a^2-12ba)

5(3a-12ba)

15a-60ba

givingiswinning | Student

`5(3a-6a^2+6a^2-12ba)`

`5(3a-12ba)`

`15a-60ba`